2012
DOI: 10.1310/hpj4712-939
|View full text |Cite
|
Sign up to set email alerts
|

Implementation and Outcome Assessment of an Inpatient Antimicrobial Stewardship Program

Abstract: Background An antimicrobial stewardship program (ASP), aiming to optimize antimicrobial usage, was implemented at a Veterans Affairs Health Care System (VA HCS). Objective The main objective of this study was to compare antimicrobial usage before and after implementation of an ASP and to assess ASP interventions. Method This retrospective study was conducted at the Fargo VA HCS. A total of 1,017 inpatient charts were reviewed for 2 distinct time periods, February through September 2008 (pre ASP) and Februa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 11 publications
1
14
0
Order By: Relevance
“…The majority of the studies that reported significant cost savings did not provide the cost of implementing the program. Table 2 summarizes studies [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ] that assessed the impact of ASP on antimicrobial use and cost of antimicrobials.…”
Section: Resultsmentioning
confidence: 99%
“…The majority of the studies that reported significant cost savings did not provide the cost of implementing the program. Table 2 summarizes studies [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ] that assessed the impact of ASP on antimicrobial use and cost of antimicrobials.…”
Section: Resultsmentioning
confidence: 99%
“…conversion (1). Of the 36 included studies, 2 were full CEAs [13,14]; 27 studies reported changes to costs and health outcomes separately [3,5,[8][9][10][12][13][14][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] and 9 reported only changes to costs [4,6,[15][16][17][18][19][20][21]. Table 1 presents the methods and results for studies that measured only cost outcomes and Table 2 presents the methods and findings of those studies that measured both a clinical as well as a cost outcome.…”
Section: Resultsmentioning
confidence: 99%
“…PAIF was the most commonly evaluated strategy (12/27; 44%) [3,8,10,13,[22][23][24][25][26][27][28]30]. In these 12 studies, the clinical outcomes measured ranged from LOS (6/12), mortality (6/12), presence of multiresistant organisms (3/12), C. difficile infection (CDI) rates (5/12) and 30-day re-admission rates (1/12).…”
Section: Cost Consequence Studies That Measured Clinical Outcomesmentioning
confidence: 99%
See 2 more Smart Citations